Sequential Engagement of FcεRI on Mast Cells and Basophil Histamine H(4) Receptor and FcεRI in Allergic Rhinitis - Shiraishi, Yoshiki (2012)
Histamine H(4) receptor (H(4)R)-deficient mice (H(4)R(−/−)), H(4)R antagonist-treated WT mice, and WT mice depleted of basophils failed to develop early (EPR) or late phase (LPR) nasal responses following allergen sensitization and challenge. Basophil transfer from WT but not H(4)R(−/−) mice restored the EPR and LPR in H(4)R(−/−) mice. Following passive sensitization with OVA-specific IgE, FcεRI(−/−) recipients of WT basophils plus OVA and histamine developed an EPR and LPR. OVA-IgE passively sensitized FcεRI(−/−) recipients of H(4)R(−/−) basophils and OVA and histamine challenge failed to develop an EPR or LPR, and basophils were not detected in nasal tissue. In contrast, recipients of basophils from IL-13(−/−) and IL-4(−/−)/IL-13(−/−) mice developed an EPR but not LPR. These results demonstrate the development of allergic rhinitis proceeded in two distinct stages: histamine release from FcεRI-activated mast cells, followed by histamine-mediated recruitment of H(4)R-expressing basophils to the nasal cavity and activation through FcεRI.